Analysis of the Impact of Import Tariff Policy on Soybean Import Demand in Indonesia - Ni Ketut Radhika Maharani Dewi D; Anandari, I Gusti Agung Ayu Apsari (CV. Lenggogeni Data Publishing, 2025)
The main objective of this study is to analyze the effect of national soybean consumption, international soybean prices, Gross Domestic Product (GDP) per capita, and import tariff policies on the volume of soybean imports in Indonesia during the period 1993–2022. This research uses a quantitative approach with a time series design and multiple linear regression analysis (OLS) to test the influence of these variables. The results indicate that simultaneously, national soybean consumption, international soybean prices, GDP per capita, and import tariff policies significantly affect soybean import demand. Partially, national soybean consumption and GDP per capita have a significant positive effect, while international soybean prices and import tariff policies have a significant negative effect on the volume of soybean imports. These findings strengthen the understanding that soybean import dependence is influenced by domestic consumption, purchasing power, global prices, and government tariff regulations. In conclusion, the management of import tariff policies needs to be designed to balance the protection of domestic producers and the availability of soybeans for consumers. Further research is recommended to examine other factors such as subsidy policies, agricultural innovation, and global trade dynamics to strengthen national food security.